Doubling of the superconducting transition temperature in ultra-clean wafer-scale aluminum nanofilms - Yeh, Ching-Chen (2024)
We studied the role of reduced dimensionality and disorder in the superconducting properties of wafer-scale aluminum (Al) nanofilms. This new generation of ultrathin films were grown using molecular beam epitaxy and depict normal-state sheet resistance at least 20 times lower than the quantum resistance h/(4e2). Defying general expectations, the superconducting transition temperature of our films increases with decreasing Al film thickness, reaching 2.4 K for a 3.5-nm-thick Al film grown on GaAs: twice that of bulk Al (1.2 K). Surface phonon softening is shown to impact superconductivity in pure ultrathin films, offering a route for materials engineering in two dimensions.